Subcellular connectomic analyses of energy networks in striated muscle. Issue 1 (December 2018) - Bleck, Christopher; Kim, Yuho; Willingham, T.; Glancy, Brian
Abstract Mapping biological circuit connectivity has revolutionized our understanding of structure-function relationships. Although connectomic analyses have primarily focused on neural systems, electrical connectivity within muscle mitochondrial networks was recently demonstrated to provide a rapid mechanism for cellular energy distribution. However, tools to evaluate organelle connectivity with high spatial fidelity within single cells are currently lacking. Here, we developed a framework to quantitatively assess mitochondrial network connectivity and interactions with cellular sites of energy storage, utilization, and calcium cycling in cardiac, oxidative, and glycolytic muscle. We demonstrate that mitochondrial network configuration, individual mitochondrial size and shape, and the junctions connecting mitochondria within each network are consistent with the differing contraction demands of each muscle type. Moreover, mitochondria-lipid droplet interaction analyses suggest that individual mitochondria within networks may play specialized roles regarding energy distribution and calcium cycling within the cell and reveal the power of connectomic analyses of organelle interactions within single cells. Assessing biological circuit connections in single cells has been intractable due to lack of appropriate tools. Here, Bleck et al. develop a method to assess mitochondrial network connectivity in muscle cells and observe clear differences consistent with differing energy requirements.